CSC571: Internet Programming / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2018)
This course introduces students to programming technologies for designing, building and publishing related to internet programming. It provides students with fundamental knowledge and techniques required to access device capabilities, current technologies and standards, operating system for Software Development Kit (SDK) and mobile programming. Upon completion, students should be able to create an efficient application for mobile devices.